Sonicated waves procedure effect on stabilizing expansive soil by nano-clay: Treat with cause - Sharo, Abdulla A.; Khasawneh, Mohammad A.; Bani Baker, Mousa; Al Tarawneh, Dana M. (Frontiers in Built Environment, 2022)
Abstract The use of hydrophilic bentonite Nano-clay to improve the geotechnical properties of expansive soils was studied. Sonic waves and manual mixing for two expansive soils (taken from two different locations in Jordan) were studied, thereafter a comparison between the results obtained from both methods was carried out. Different percentages of Nano-clay were added to the two soils: 0, 0.1, 0.3, 0.5, 0.8, 1, 1.5, and 2.5% by dry weight of soil. Their impact on compaction, Unconfined Compression Strength (UCS), and Free Swell Index (FSI) were investigated. For both methods of mixing, adding Nano-clay to the soils resulted in a significant enhancement in strength and a reduction in swell properties of the soils. The UCS results of sonicated samples treated with 0.5% of Nano-clay addition showed an increase of 27%-57%, and a reduction in FSI by 41%- 46.5%. Nevertheless, the UCS of non-sonicated samples treated with 1% of Nano-clay showed an increase of 19.3-28.5%, and a reduction in FSI by 37.3-44.3%.